2020
DOI: 10.1099/ijsem.0.004200
|View full text |Cite
|
Sign up to set email alerts
|

Oleiliquidispirillum nitrogeniifigens gen. nov., sp. nov., a new member of the family Rhodospirillaceae isolated from oil reservoir water

Abstract: A novel Gram-staining-negative, spiral-shaped bacterium, designated strain 64-1T, was isolated from oil reservoir water collected from Liaohe oilfield, north-eastern China. Growth occurred at 15–55 °C and pH 6.0–10.0. The sole respiratory quinone was Q-10. The predominant cellular fatty acids were summed feature 8 (C18 : 1  ω7c /C18 : 1  ω… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Differential phenotypic characteristics of strain Y-M2 T compared with phylogenetically closed families within the order Rhodospirillales Taxa: 1, Oleispirillaceae fam. nov. (this study); 2, 'Magnetospirillaceae'[15,28,31,59,60]; 3, 'Novispirillaceae'[10,[61][62][63]; 4, Rhodospirillaceae[60,[64][65][66][67][68][69][70][71][72][73][74][75]. +, Positive; −, negative; +/−, positive in some species but negative in others; w, weak; nd, not determined.…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…Differential phenotypic characteristics of strain Y-M2 T compared with phylogenetically closed families within the order Rhodospirillales Taxa: 1, Oleispirillaceae fam. nov. (this study); 2, 'Magnetospirillaceae'[15,28,31,59,60]; 3, 'Novispirillaceae'[10,[61][62][63]; 4, Rhodospirillaceae[60,[64][65][66][67][68][69][70][71][72][73][74][75]. +, Positive; −, negative; +/−, positive in some species but negative in others; w, weak; nd, not determined.…”
mentioning
confidence: 69%
“…Genomic studies have revealed that nitrogen fixation-related genes constitute a nitrogen fixation cluster, such as the 17 nif genes ( nifQ , nifA , nifL , nifH , nifD , nifK , nifT , nifY , nifE , nifN , nifX , nifS , nifU , nifW , nifZ , nifM , and nifF ) distributed in a 49 kb region in Stutzerimonas stutzeri A1501 T [29, 30]. Previous studies have demonstrated that all nitrogen fixation bacteria in the order Rhodospirillales carry nif gene clusters, and no vnf or anf cluster has been identified in these species [6–8, 13, 19, 28, 31].…”
Section: Introductionmentioning
confidence: 99%
“…2). Further comparative analysis indicates that strain XQGS-1 shares low 16S rRNA gene sequence identities with all reported bacteria, such as Caenispirillum salinarum (identity, 92.6%) (33), Oleiliquidispirillum nitrogeniifigens (identity, 92.5%) (34), and MTB clone WYH-37 (identity, 92.5%) (31). Such differences are less than the genus criterion level of 94.5% (35), which indicates that strain XQGS-1 represents a novel MTB species in a novel genus from the Alphaproteobacteria class.…”
Section: Resultsmentioning
confidence: 99%
“…1). Thus, the family Magnetospirillaceae should include the following genera: Magnetospirillum, Paramagnetospirillum, Phaeospirillum, Oleiliquidispirillum (Li et al, 2020) and the genus Telmatospirillum (Sizova et al, 2007) currently classified in the family Rhodospirillaceae.…”
Section: Taxonomic Revision Of the Rhodospirillales Familiesmentioning
confidence: 99%